The predictive effects of protection motivation theory on adaptive behavior towards urban air quality - Sahrir, Syazwani; Abdullah, Ahmad Makmom; Ponrahono, Zakiah; Sharaai, Amir Hamzah (Readers Insight Publisher, 2019)
In urban areas, the rigid division of residential, commercial, employment and recreational areas forms a reliance on road transport, which leads to high levels of emission that gradually affects the quality of the urban environment. We establish the Protection Motivation Theory (PMT) as a framework for explaining adaptive behavioural responses among urban communities in Malaysia. Participants (N = 450) answered to face-to-face questionnaire survey, and the results specify establishment for the proposed model, with perceived vulnerability (H1) (ß = 0.246, t = 4.534, P=0.000) and and self-efficacy (H3) (ß = 0.510, t = 9.653, P=0.000) positively predicting adaptive behaviour on urban air pollution. The results presented that these structures were able to predict 47% of the variance of adaptive behaviour. The study establishes a significant contribution to the literature by contributing an indication of PMT as an ideal framework for adaptive behavioural responses on urban air pollution.